2009 International Conference on Environmental Science and Information Application Technology 2009
DOI: 10.1109/esiat.2009.408
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Differentiation of Fenneropenaeus Penicillatus Populations by Allozyme Analyses

Abstract: Genetic diversity was investigated using assay of vertical slab ployacrylamide gel electrophoresis for the nine populations of Fenneropenaeus penicillatus. The results showed high levels of genetic diversity in each of the nine F. penicillatus populations. The mean number of alleles per locus ranged from 1.3333 to 1.6667, with a average of 1.4148. And the mean effective number of alleles per locus ranged from 1.1447 to 1.2094, with a average of 1.1664. The average of percentage of polymorphic loci was 26.67%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Their long geographic distance from the spawning ground and their low genetic diversity explain why they clustered together. This was consistent with that by allozyme technique (Zhang et al, 2009). In addition, the genetic distance between Xiamen and Ningde is larger than that between Xiamen and Shenzhen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Their long geographic distance from the spawning ground and their low genetic diversity explain why they clustered together. This was consistent with that by allozyme technique (Zhang et al, 2009). In addition, the genetic distance between Xiamen and Ningde is larger than that between Xiamen and Shenzhen.…”
Section: Discussionsupporting
confidence: 91%
“…penicillatus which suggested a low level of genetic differentiation and a high level of gene fl ow ( G ST =0.032 7; N m =11.735 8)(Zhang et al, 2009). Our fi ndings are consistent with a previous AFLP study on Litopenaeus vannamei , however, which showed that both the genetic differentiation and the gene fl ow were high ( G ST =0.363 8; N m =0.937 2)…”
mentioning
confidence: 99%